Pengaruh Kepuasan Kerja Dan Komitmen Organisasi Terhadap Turnover Intention di PT. Indo Acidatama - Hidayahti, Yunita Nur; , Dr. Anton Agus Setyawan, SE., M.Si (2016)
The aim of this study: (1) To analyze the effect of job satisfaction on employee turnover intention. (2) to analyze the influence of organizational commitment to employee turnover intention. (3) To analyze the effects of job satisfaction and organizational commitment significant effect together towards employee turnover intention PT.Indo Acidatama Kebakkramat. This type of research is the field surveys, the study population is all employees of PT. Indo Acidatama Kebakkramat, samples in this study were 100 employees in PT.Indo Acidatama Kebakkramat, sampling techniques using simple random sampling. Data were analyzed using: (1) test the research instrument, namely the validity and reliability, (2) Testing multiple linear regression, (3) Test the hypothesis, that the t test, F test and coefficient of determination. In conclusion, (1) there is a negative and significant effect of job satisfaction on employee turnover intention, (2) there is a significant negative influence and organizational commitment to employee turnover intention, (3) there is a significant influence employee satisfaction and organizational commitment together against turnover intention of employees of PT. Indo Acidatama Kebakkramat.